8. THE VALUE OF KIDs SCORE IN THE PROGNOSIS OF CLINICAL PREGNANCY AFTER THE TRANSFER OF DAY-5 FROZEN EMBRYOS CULTURED USING THE TIMELAPSE SYSTEM AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL. (Vietnam Journal of Community Medicine, 2025)
Objectives: To analyze the performance of the KIDs score in predicting of clinical pregnancy outcome after a single frozen blastocyst embryo transfer using the Timelapse system at Hanoi Obstetrics and Gynecology Hospital.Materials and methods: Descriptive study on 221 patients with frozen blastocyst embryo transfer using the Timelapse system for embryo incubation from June 2023 to May 2024 at Hanoi Obstetrics and Gynecology Hospital.Results: The rates of β-HCG (+), clinical pregnancy, and ongoing pregnancy were 69.2%, 62.9% and 56.1%, respectively. The average KIDs score was 7.3 ± 1.74 points. The average KIDs score was higher in the pregnant group than in the non-pregnant group (7.6 ± 1.5 points vs 6.8 ± 2.1 points, p = 0 < 0.05). In both the non-PGT group and the group with abnormal PGT results, the average KIDs score was higher in the pregnant group than in the non-pregnant group (8.0 ± 1.3 points vs 6.8 ± 2.4 points, p < 0.05 and 7.8 ± 1.5 points vs 6.1 ± 1.8 points, p < 0.05). The KIDs score cut-off value for predicting clinical pregnancy was 7.15, with a sensitivity of 65.5%, specificity of 53.7%, and an AUC of 0.609.Conclusions: The KIDs score in the Timelapse system model worked well for prediction of clinical pregnancy, with the average KIDs score was higher in the pregnant group than in the non-pregnant group.
Keywords: Timelapse system; KIDs score; frozen blastocyst embryo transfer